HOW TO TEACHING THE EARLY READING TO MENTALLY DISABLE STUDENTS IN ELEMENTARY SCHOOL? - Kurniaman, Otang; Eka Dewi, Yunita; Noviana, Eddy; Munjiatun, Munjiatun (Wahana Sekolah Dasar, 2023)
Children with mentally disable is a children who has cognitive barriers experience,  in early reading it is often disturbed by the difficulty of remembering the letters, and also connecting phonemes with the objects. This article presents innovations on how to teach early reading to mentally disable students in elementary schools. The purpose of this study is to provide an overview of how teachers teach early reading to mentally retarded students in elementary schools. This study uses qualitative methods that describe how teachers teach early reading, with the subject of mentally disable classroom teachers at SDLB Kasih Ibu Pekanbaru. Data collection techniques are through observation and interviews. The results of research observation planning data, the teacher gives emphasis to the letters and shows the image in accordance with the initial letter given emphasis, and linking the material with everyday life that can be found by students using an easy to understand reading method. Observation data of the presentation component, the teacher in explaining the material using simple language, by verbal media and giving emphasis to the letters that students’ will be read. The conclusion of this study is the application of one component of the skills explains in teaching initial reading, the component of material presentation in the first day's observations has been going well.